DEVELOPING A GLOBAL DIVERSITY PROFILE TO STRENGTHEN CIVIC LITERACY IN STUDENTS THROUGH THE DEVELOPMENT OF SCHOOL CULTURE - Nurainun; Fazli Rachman; Liber Siagian; Surya Dharma; Oksari Anatasya Sihaloho (PRODI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN STKIP PGRI SUMENEP, 2025)
This article aimness how the development of students’ global diversity profiles can be fostered through school culture as a means of strengthening civic literacy. The global diversity profile is one of the essential characteristics that students must possess. It is particularly important for citizens living in communities characterized by religious, ethnic, racial, and cultural diversity. This study was conducted at Gajah Mada Private Senior High School, a multicultural school in Medan that embraces diversity in religion, ethnicity, and culture. The research employed a qualitative method with a descriptive approach.The research subjects include the principal, vice principal, Pancasila Education teacher, Japanese and English language teachers, administrative staff, and students. Data collection techniques include observation, interviews, and documentation. The data analysis used in this study is the spiral data analysis model, which outlines six stages in analyzing qualitative data. These stages include: (1) Data Collection, (2) Data Managing, (3) Reading and Memoing, (4) Describing, Classifying, and Interpreting, (5) Representing and Visualizing. The findings of this study indicate that the development of a globally diverse profile to enhance students’ civic literacy at Gajah Mada Private Senior High School is designed through habitual practices and the creation of an inclusive environment. The implementation of this development is integrated into both intracurricular and cocurricular activities. Moreover, the cultivation of a globally diverse profile is not only focused on shaping students' understanding of national diversity but also extends to an international context